THE RELATIONSHIP BETWEEN ANDRAGOGY AND PEDAGOGY IN THE ROLES OF THE ANDRAGOGICAL ENGLISH LANGUAGE TEACHER - Горана З. Билић Пријић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2013)
The beginnings of andragogy and the science of foreign language teaching emerged from the universal and undifferentiated pedagogical theoretical thought about education. Mid 20th century saw a struggle to differentiate the andragogical theory and practice from the general pedagogical thought. Today it seems that the focus is no longer on differentiating and opposing andragogy and pedagogy, but rather on their connections and the development through their mutual influence. Andragogy and pedagogy are seen as two points on the same continuum. In the development of the roles of the andragogical English language teacher, the andragogical and theoretical influences are interwoven, with a clear tendency for teaching and the role of the teacher to become increasingly andragogical. The aim of this paper is to show how the pedagogical and andragogical theoretical thought affects the role of the andragogical teacher of the English language through history, with the focus on the roles of the andragogical English language teacher today.